Promoting Students’ Speaking Proficiency through Communicative Activities. Case Study of Department of English, Faculty of Education, Champasack University: https://doi.org/10.69692/SUJMRD100148 - SORKEOMANY, Bounsong (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The study was to examine the effectiveness of the communicative activities (CAs), and to explore the students’ attitudes and perceptions towards the application of communicative activities by two groups before treatment and after treatment. The Quasi-experimental design was used. There were 54 total English third-year students at the English Department, Faculty of Education, Champasack University. There were two groups of participants: the “Experimental group” (30 students) and the “Control group” (24 students). The experimental teaching was conducted for 36 hours within a 9-week period in 4 cycles with the uses of the three communicative activities; group discussion, role-play, and debate which including Pre-Posttest, rubric of speaking proficiency, attitude and perception questionnaire, observation checklist, ten sub-commutative activities within 4 debate periods were employed for this study. Pre-posttest and questionnaires were given to students in both experimental and control groups to check the reliability of the test, this research used three senior score raters to measure the students’ speaking proficiency by using the rubric of speaking proficiency. The observation checklist was noted by the researcher in every class within the communicative activities used. The data were statistically analyzed by t-test independent and paired-t test for the dependent sample by comparing the mean scores of the pretest and posttest to determine whether there was a significant difference between the experimental and control groups. Moreover, the students were required to respond the attitude and perception questionnaire to explore their attitudes and perceptions towards the communicative activities. Two groups compared the findings of the test; it was found that the CAs were effectiveness to improve students’ speaking proficiency as can be seen through the increasing of the test score of the experimental group, which started from 74.43 to 83.90 (9.47) with the significant level of p < .05. In addition, the majority of the students had positive attitude and perception towards the effectiveness of the communicative activities used.